CREATIVE LEADERSHIP BASED ON YONISOMANASIKARA OF SCHOOL ADMINISTRATORS UNDER ROI ET PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Ngamsaeng, Nanthawan; Phrakhruvichitpanyaphorn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of the research were 1) to study the creative leadership based on Yonisomanasikara of school administrators under Roi Et primary education service area 1 according to the teacher's concept 2) to compare creative leadership based on Yonisomanasikara of school administrators under Roi Et primary education service area 1 according to the teachers’ concept, classified by educational level, work experience, and school size 3) to study the guidelines for developing creative leadership based on Yonisomanasikara of school administrators under Roi Et primary education service area 1. The sample group in this research were 335 administrators and teachers and 5 interviewees. The research instrument was a 5-point Rating scale questionnaire, and the semi-structured interview. The statistics used were frequency, percentage, mean, standard deviation and the t-test (Independent Samples), One-way analysis of variance (ANOVA), using F-test statistics. If statistically significant difference were found, multiple comparison tests were performed using Scheffe’s. Method The research results were as follows: 1) The level of creative leadership based on Yonisomanasikara of school administrators under Roi Et primary education service area 1 overall was at a high level. The aspect with the highest mean was Team inquiry, followed by collecting analyzing and interpreting data and the aspect with the lowest mean was asking questions. 2) The Comparison of the level of opinions toward the creative leadership based on Yonisomanasikara of school administrators under Roi Et primary education service area 1, classified by educational level, work experience, and school size, overall and each aspect were significantly different at the .05 level. 3) Guidelines for the development of creative leadership based on Yonisomanasikara of school administrators. From the in-depth interviews with school administrators, it was found that administrators should encourage teachers to create innovations to develop teaching and learning that were suitable for changing context. The executives set the objectives and goals of the work that were accurate and clear together, let teachers know how to solve problems in situations, had a clear forward-looking vision.